Cardiovascular risks in relation to daidzein metabolizing phenotypes among Chinese postmenopausal women. - Zhao-min Liu (Public Library of Science (PLoS), 2014)
Background Studies suggested that the inter-individual differences in metabolizing isoflavone daidzein to equol or O-desmethylangolensin (ODMA) might explain the inconsistency of the soy/isoflavones efficacy on cardiovascular health. Objectives The study aims to evaluate the relationship between equol and ODMA phenotypes and cardiovascular risks with habitual isoflavone consumption in Chinese postmenopausal women. Methods This is a cross-sectional study among 726 prehypertensive postmenopal women who were screened for a randomized controlled trial. 648 women returned a daidzein-challenged urine samples for determination of equol and O-DMA production. 595 attended clinic visits for assessment of cardiovascular risks including body composition, blood pressure (BP), serum lipids, uric acid, high sensitivity C-reactive protein (hs-CRP), fasting glucose and free fatty acid (FFA). Results The prevalences of equol and O-DMA producers were 53.2% and 60.9% respectively. Equol producers had higher fat free mass (p = 0.001), lower systolic (p = 0.01) and diastolic (p = 0.01) BP, serum triglyceride (p = 0.023), hs-CRP (p = 0.015) and FFA (p = 0.001) than non-producers. O-DMA producers had lower body fat% (p = 0.032), SBP (p = 0.02), total cholesterol (p = 0.002) than non-producers. The significant differences remained after further adjustment for potential confounders. The habitual soy isoflavones intake had little relation to cardiovascular risk factors in either equol/O-DMA producer phenotypes. Conclusion Equol/O-DMA producers had more favorable cardiovascular risk profiles than non-producers in prehypertensive postmenopausal women.